Treatment of varicocele in children and adolescents: a systematic review and meta-analysis from the European Association of Urology/European Society for Paediatric Urology guidelines panel - Silay, Mesrur Selcuk; Stein, Raimund (European urology, 2019)
Context - The benefits and harms of intervention (surgical or radiological) versus observation in children and adolescents with varicocele are controversial. - Objective - To systematically evaluate the evidence regarding the short- and long-term outcomes of varicocele treatment in children and adolescents. - Evidence acquisition - A systematic review and meta-analysis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement. A priori protocol was registered to PROSPERO (CRD42018084871), and a literature search was performed for all relevant publications published from January 1980 until June 2017. Randomized controlled trials (RCTs), nonrandomized comparative studies (NRSs), and single-arm case series including a minimum of 50 participants were eligible for inclusion. - Evidence synthesis - Of 1550 articles identified, 98 articles including 16 130 patients (7-21 yr old) were eligible for inclusion (12 RCTs, 47 NRSs, and 39 case series). Varicocele treatment improved testicular volume (mean difference 1.52ml, 95% confidence interval [CI] 0.73-2.31) and increased total sperm concentration (mean difference 25.54, 95% CI 12.84-38.25) when compared with observation. Open surgery and laparoscopy may have similar treatment success. A significant decrease in hydrocele formation was observed in lymphatic sparing versus non-lymphatic sparing surgery (p=0.02). Our findings are limited by the heterogeneity of the published data, and a lack of long-term outcomes demonstrating sperm parameters and paternity rates. - Conclusions - Moderate evidence exists on the benefits of varicocele treatment in children and adolescents in terms of testicular volume and sperm concentration. Current evidence does not demonstrate superiority of any of the surgical/interventional techniques regarding treatment success. Long-term outcomes including paternity and fertility still remain unknown. - Patient summary - In this paper, we review benefits and harms of varicocele treatment in children and adolescents. We found moderate evidence that varicocele treatment results in improvement of testicular volume and sperm concentration. Lymphatic sparing surgery decreases hydrocele formation. Paternity and fertility outcomes are not clear.
Available online 10 October 2018
Gesehen am 06.09.2019